2021
DOI: 10.1093/hmg/ddab338
|View full text |Cite
|
Sign up to set email alerts
|

An epileptic encephalopathy associatedGABRG2missense mutation leads to pre- and postsynaptic defects in zebrafish

Abstract: Mutations in the γ-aminobutyric acid type A (GABAA) receptor γ2 subunit gene, GABRG2, have been associated with a variety of epilepsy syndromes. A de novo mutation (c.T1027C, p.F343L) in GABRG2 was identified in a patient with early onset epileptic encephalopathy. Zebrafish overexpressing mutant human GABRG2 (F343L) subunits displayed spontaneous seizure activity and convulsive behaviors. In this study, we demonstrated that Tg (hGABRG2F343L) zebrafish displayed hyperactivity during light phase with normal circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 59 publications
2
7
0
Order By: Relevance
“…Preclinical studies showed that zebrafish overexpressing mutant human GABRG2 (p.(Phe343Leu)) subunits mimicked the human DEE phenotype. 29,30 Moreover, gabrg2 −/− zebrafish mutants are prone to light-induced seizures and respond well to VPA 31 ; mimicking the phenotype and drug response of our patient.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Preclinical studies showed that zebrafish overexpressing mutant human GABRG2 (p.(Phe343Leu)) subunits mimicked the human DEE phenotype. 29,30 Moreover, gabrg2 −/− zebrafish mutants are prone to light-induced seizures and respond well to VPA 31 ; mimicking the phenotype and drug response of our patient.…”
Section: Discussionsupporting
confidence: 64%
“…Most Sunflower syndrome patients have difficult to treat epilepsy, which could also be the case for our patient although longer follow‐up is needed to confirm this constellation. Preclinical studies showed that zebrafish overexpressing mutant human GABRG2 (p.(Phe343Leu)) subunits mimicked the human DEE phenotype 29,30 . Moreover, gabrg2 −/− zebrafish mutants are prone to light‐induced seizures and respond well to VPA 31 ; mimicking the phenotype and drug response of our patient.…”
Section: Discussionsupporting
confidence: 52%
“…To detect the effect of locations of mutations on phenotypes, we compared the locomotive activity of different mutant GABRG2 transgenic zebrafish. In the previous research, we generated F343L and I107T transgenic zebrafish with spontaneous seizures 6,10 . In this research, the distance traveled in 30 min at 5 dpf was compared in the above three transgenic lines and the data showed that all mutant zebrafish traveled more than the WT control group, showing an epileptic phenotype.…”
Section: Resultsmentioning
confidence: 93%
“…In the previous research, we generated F343L and I107T transgenic zebrafish with spontaneous seizures. 6,10 In this research, the distance traveled in 30 min at 5 dpf was compared in the above three transgenic lines and the data showed that all mutant zebrafish traveled more than the WT control group, showing an epileptic phenotype. Among the three mutant zebrafish models, the I107T line traveled the most while the P282S line traveled the least, and the difference between the two groups was significant (1774 ± 94.55 mm in the I107T group vs. 1125 ± 106.9 mm in the P282S group, p = 0.0010, Figure 4A), indicating a less active phenotype induced by P282S mutation.…”
Section: Comparison Of Different Mutant Gabrg2 Transgenic Zebrafish M...mentioning
confidence: 87%
“…RNA-sequencing analysis of mutation of GABRA1 in zebrafish larval brains identified a marked downregulation of genes encoding inhibitory synaptic components as well as proteins involved in axon guidance. Immunocytochemical analysis revealed a marked decrease in the accumulation of GABA synaptic markers; consistently, transgene GABRG2 mutation resulted in postsynaptic and presynaptic defects ( 64 , 65 ). GABRG2 was found to be associated with suicidal behavior and major depressive disorder ( 66 ).…”
Section: Discussionmentioning
confidence: 91%